Improving Visual Arts Learning Outcomes Through the Demonstration Method for Fourth-Grade Students at SDN Kemayoran 1 Bangkalan - Alfin, Aprilia Halisa; Istiqomaturrobiah , Asri; Rania, Nabila (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2024)
This Classroom Action Research (CAR) originates from the issue of low student performance in Cultural Arts and Crafts, particularly in drawing topics. The primary reasons for this are the traditional teaching methods and insufficient modeling by the teacher, which make the material delivery unclear and overly teacher-centric. The objective of this research is to enhance students' engagement and performance in Cultural Arts and Crafts, specifically in batik drawing, for the fourth-grade class C at Kemayoran 1 Bangkalan State Elementary School by implementing the demonstration method. The strength of this study lies in its shift from a teacher-centered to a student-centered learning approach through the use of demonstrations. This method encourages students to actively seek, discover, and deepen their understanding independently. The research was conducted over three cycles, with data collected via interviews, questionnaires, tests, observations, and documentation from both teachers and students. The findings indicate a significant improvement in students' engagement and performance with the use of the demonstration method. Therefore, it can be concluded that applying the demonstration method effectively boosts students' learning activities and achievements in Cultural Arts and Crafts, especially in batik drawing, in the fourth-grade class C at Kemayoran 1 Bangkalan State Elementary School.